Code-switching used by English teachers in teaching EFL students - Andi Rustandi; Febriani (Scopus ID 57217300982), R Bunga; Sevia Fauziah (UNIB Press, 2023)
This study aims to investigate: (1) the types of code-switching used by English teachers in teaching the classroom; and (2) the frequency of code-switching functions used by English teachers in teaching activities. According to Poplack’s theory, there are three types of code-switching: inter-sentential switching, intra-sentential switching, and tag switching. In addition, there are also three functions of code-switching that will be found in classroom activities according to Sert’s theory: topic switch, affective function, and repetitive function. This study was conducted using a qualitative method with a case study approach. The participant in this study was an English teacher at one of the Islamic junior high schools in Ciamis. To determine the participant, the writer used the purposive sampling technique. Data collection in this study was carried out through observation and recording. The writer conducted observation twice, and then recording was used to analyze the data. The results show: (1). The teacher did all the types of code-switching according to Poplack’s theory in her teaching activities, namely, inter-sentential switching, intra-sentential switching, and tag switching. (2). The code-switching function that was dominantly used by English teachers was the topic switch function, with 109 cases, or 82%, while the results of affective and repetitive functions were equal.